Truncated BAM receptors interfere the apical meristematic activity in a dominant negative manner when ectopically expressed in Arabidopsis. (April 2018) - Wang, Caili; Yang, Heyu; Chen, Lincai; Yang, Shaohui; Hua, Deping; Wang, Jiehua
Highlights: Functional redundancy makes it difficult to discern the role of individual members of receptor-like kinase family by a genetic approach. BAM protein without its signal peptide or the kinase domain interfered with the SAM activity and phenotypically resembled triple bam mutations. The dominant-negative effect of a truncated BAM protein could be achieved when driven by AtBAM1 promoter, but not by AtCLV1 promoter. When introduced into a clv1-4 background, BAMΔ proteins abolished the clv phenotype by suppressing the transcriptional level of clv1-4 . Expression of a truncated plant LRR receptor kinase could potentially be used to reveal its in vivo function in signal transduction. Abstract: Small, secreted signaling peptides that are perceived by receptor-like kinases (RLKs) constitute an important regulatory mechanism in plant organ formation and stem cell maintenance. However, functional redundancy at the level of both ligand and receptor families often makes it difficult to clearly discern the role of individual members by a genetic approach. Here, we show that driven by a constitutive CaMV 35S promoter, a truncated BAM protein (BAMΔ) that lacks either the signal peptide (SP) or the cytoplasmic kinase (Ki) domain could cause defective shoot apical meristem (SAM) maintenance, which phenotypically resembled the triple bam mutant. Such a dominant-negative effect could also be achieved when the same transgene was driven by the native AtBAM1 promoter, but not by the CLV1 promoter. When introduced into a clv1-4 background, BAMΔ proteins abolished the typical clv phenotype by suppressing the transcriptional level of clv1-4 . In addition to a clear reduction in root length and a decreased number of meristematic cells, the 35S:BAMΔ transgenic seedlings exhibited considerable resistance to CLE40p- but not to CLV3p-mediated root growth inhibition, implying that BAMs play key roles in the regulation of proximal meristem activity in root through CLE40 peptide. Findings present here not only provide evidence that truncated BAM proteins are strongly dominant negative in regulating apical meristem development but also propose that expression of a truncated version of plant LRR receptor kinase could potentially be used as a powerful tool to reveal its in vivo function in signal transduction.